2021
DOI: 10.1029/2021wr029595
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Drivers Responsible for Flooding in Africa

Abstract: Africa is severely affected by floods, with an increasing vulnerability to these events in the most recent decades. Our improved preparation against and response to this hazard would benefit from an enhanced understanding of the physical processes at play. Here, a database of 399 African stream gauges is used to analyze the seasonality of observed annual maximum flood, precipitation and soil moisture between 1981 and 2018. The database includes a total of 11,302 flood events, covering most African regions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 95 publications
4
31
1
Order By: Relevance
“…Tramblay et al. (2021) reported that wet antecedent conditions prior to extreme precipitation are less relevant to flood generation than multiday precipitation events. Consistently, our results show multiday precipitation is the prominent mechanism compared to compound extremes in driving high flows.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tramblay et al. (2021) reported that wet antecedent conditions prior to extreme precipitation are less relevant to flood generation than multiday precipitation events. Consistently, our results show multiday precipitation is the prominent mechanism compared to compound extremes in driving high flows.…”
Section: Resultsmentioning
confidence: 99%
“…The figure shows the mean values of the 39 catchments examined in this study. Hettiarachchi et al, 2019;Tramblay et al, 2021). Therefore, in small catchments across the west coast and southern India, extreme precipitation events alone have the potential to cause flooding.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CHIRPS precipitation estimates have been validated across different regions in Africa (Dinku et al 2018;Satgé et al 2020). It has also been used in several studies in Africa, e.g., (1) to analyse long-term trends in precipitation (Muthoni et al 2019;Alemu & Bawoke 2020), (2) for hydrological modelling (Dembélé et al 2020;Larbi et al 2020), (3) for flood studies (Elagib et al 2021), and (4) to evaluate the drivers of flood events (Tramblay et al 2021). CHIRPS data were downloaded free of charge from https://climateserv.servirglobal.net.…”
Section: Chirps Precipitationmentioning
confidence: 99%
“…One way of exploring the relative importance of these drivers is by analyzing flood seasonality, defined as the day of the year that floods occur. A coincidence in the timing of floods and their drivers can be used as a proxy for the causality of flood generation (Parajka et al., 2010; Sivapalan et al., 2005; Tramblay et al., 2021).…”
Section: Introductionmentioning
confidence: 99%